Measurements of total energy expenditure provide insights into the validity of dietary measurements of energy intake. - Black, A; Prentice, A; Goldberg, G; Jebb, S; Bingham, SA; Livingstone, M; Coward, W (1993)
The quantification of errors inherent in methods of measuring dietary intake has been handicapped by the absence of independent markers for testing their validity. The doubly labeled water technique permits a precise measure of energy expenditure in free-living persons. Because energy expenditure must equal energy intake in populations in energy balance, this technique may be used to validate the assessment of energy intake. A series of studies demonstrated good agreement between mean energy intake and mean energy expenditure when food intake was recorded by observers or when it was self-reported by normal-weight, self-selected, highly motivated volunteer subjects using weighed records. However, in randomly recruited men and women, energy intake by weighed records was 82% and 81%, of energy expenditure, respectively, indicating underestimation of habitual intake. Men and women in the lowest third of reported intake recorded energy expenditure of only 69% and 61%, respectively. Reported intake of obese and previously obese women was only 73% and 64% of expenditure, whether measured by weighed record or by diet history, confirming suspicions that these subjects misrepresented their intake. Acceptable weighed records were obtained from 7- and 9-year-olds whereas 15- and 18-year-olds underestimated intake. Diet histories taken from the same children tended to overestimate intake. These studies suggest that, ideally, all dietary studies should include independent measures of validity.